Films deposited from reactive sputtering of aluminum acetylacetonate under low energy ion bombardment - Battaglin, Felipe Augusto Darriba [UNESP]; Prado, Eduardo Silva [UNESP]; Caseli, Luciano; Da Silva, Tiago Fiorini; Tabacniks, Manfredo Harri; Da Cruz, Nilson Cristino [UNESP]; Rangel, Elidiane Cipriano [UNESP] (FapUNIFESP (SciELO), 2017)
Films were deposited from aluminum acetylacetonate (Al(acac)3) using a methodology involving reactive sputtering and low energy ion bombardment. The plasma was generated by the application of radiofrequency power to the powder containing electrode and simultaneously, negative pulses were supplied to the electrode where the substrates were attached. It was investigated the effect of the duty cycle of the pulses (Δ) on the properties of the coatings. Association of ion bombardment to the deposition process increased film thickness, structure reticulation and organic content. Ions from the deposition environment were implanted at the film-air interface or underneath it. Morphology and topography were altered depending on Δ. Considering the enhancement of Δ, it affected the flux of ions reaching the depositing interface and then the deposition rate, H content, crosslinking degree and surface microstructure. Alumina groups were detected in the infrared spectra, whereas the precipitation of amorphous alumina was confirmed by X-ray diffraction.
Keywords: Aluminum acetylacetonate; Duty cycle; Ion bombardment